Hazard Map of Rincón de la Vieja Volcano, Costa Rica: Qualitative Integration of Computer Simulations and Geological Data - Segura, Yemerith Alpízar; Arce, Mario Fernández; Umaña, Carlos Ramírez; Alpízar, Deina Arroyo (Anuário do Instituto de Geociências, 2019)
A volcanic hazards map was prepared for Rincón de la Vieja volcano, based on the integration and analysis of existing information, computational models and fieldwork data. Until 2018, this volcano did not have an official volcanic hazard map, necessitating the application of volcanic disaster risk management to territorial planning of the region. Results of this work will serve as a tool for the decision-making institutions, providing guidance to apply better practices for land use, planning and perform risk management, considering the volcanic hazard component. The document was prepared based on three main data sources: 1. Data collected in the field, 2. Deterministic models and; 3. Previously published data. The result obtained is an integrated qualitative map (Calder et al., 2015), which shows the main volcanic threats in the short and medium term, which can affect the study area as a result of the eruptive activity of Rincón de la Vieja.